Estudio fitosociológico de la vegetación de una zona de contacto Chaco-Cerrado en Santa Cruz (Bolivia)- - Fuentes, Alfredo; Navarro, Gonzalo (Lazaroa, 2000)
Fuentes, A. & Navarro, G. Phytosociological study of the vegetation in a Chaco-Cerrado contact area in Santa Cruz (Bolivia). Lazaroa 21: 73-109 (2001). The phytosociological study in an area of the eastern lowlands of Santa Cruz, Bolivia, describes the regional forest associations on the Chaco alluvial plain of the adjacent Brazilian Pre-Cambrian Shield as well as those of the aquatic vegetation belonging to the Brazilian-Paranean and Chaco biogeographic regions. Three forest associations are recognised in the Brazilian Shield: 1. Priogymnantho hasslerianae-Callisthenetum fasciculatae ass. nova (Cerrado woodland), 2. Machaerio scleroxyloni-Acosmietum cardenasii ass. nova («Chiquitano» dry forest) and 3. Viticio cymosae-Carinianetum ianeirensis ass. nova («Chiquitano» hygrophilous forest). There are four recognised forest associations on the Chaco plain: 1. Diplokelebo floribundae-Phyllostylonetum rhamnoidis ass. nova (transitional Chaco forest), 2. Diplokelebo floribundae-Trithrinacetum schizophyllae ass. nova (poorly drained Chaco thorn palm woodland), 3. Microlobio paraguensis-Copernicietum albae ass. nova (seasonally flooded palm woodland) and 4. Cratevo tapiae-Albizietum inundatae ass. nova (Chaco riparian woodland). There are also recognised associations of aquatic vegetation: 1. Lemno aequinoctialis-Wolfffielletum lingulatae (pleustophytic association), 2. Eichhornietum crassipedis (pleustohelophytic association), 3. Althernanthero aquaticae-Paspaletum elephantipes ass. nova (helophytic association) and 4. Mimoso chaetospherae-Ipomoeetum fistulosae ass. nova (helophytic nitrophilous dwarf-scrubland). The diagnoses, supported by their respective phytosociological tables, are presented here in unpublished, provisional and previously constructed syntaxonomic frameworks.